An enigma: A meta-analysis reveals the effect of ubiquitous microplastics on different taxa in aquatic systems - Moyo, Sydney (Frontiers in Environmental Science, 2022)
Microplastics are ubiquitous in aquatic ecosystems globally, with tropical freshwater systems underrepresented in the literature. The ubiquity of microplastics may affect the growth, reproduction, and survival of organisms in aquatic systems; however, the data on the potential effects of microplastics on aquatic organisms is tentative. In the current study, I conducted a meta-analysis using published data to examine the impacts of microplastic exposure on functional traits (i.e., feeding, growth, reproduction, survival) of fish and aquatic invertebrates. The data revealed that while there were within-taxa negative effects on traits such as reproduction and growth some effect sizes were low, suggesting that the exposure to microplastics may vary across taxa. Globally, negative effects on growth, reproduction, and even survival were evident in some taxa (e.g., bivalves, crustaceans) Considering feeding habits, negative effects of microplastic were more pronounced in bacterivores, omnivores, predators, and filter feeders compared to shredders. In tropical freshwater systems, microplastics had no significant effects on the feeding, growth, reproduction, and survival of aquatic organisms. It is worth noting that organisms that are passive feeders (e.g., bivalves) may be particularly susceptible to exposure to microplastic pollution, which in turn may have long-lasting effects on the stability of lacustrine and lotic food webs. Because microplastics may impart more chronic effects than acute effects, future works must include understudied regions of the world (e.g., freshwater systems) and must emphasize the subtle role that microplastics may play on the physiology and behavior of organisms in the long term.